PEMAHAMAN MAJLIS TAFSIR AL-QUR’AN (MTA) DI DUSUN KAMBOJA DESA BANDAR KLIPPA KECAMATAN PERCUT SEI TUAN TERHADAP HADIS TENTANG MENAFSIRKAN ALQURAN DENGAN AL-RA’Y - Manik, Zulfirman (SHAHIH (Jurnal Kewahyuan Islam), 2020)
Majlis Tafsir Al-Qur?an (MTA) is an Islamic education and preaching institution based in Surakarta, founded by the late Ustadz Abdullah Thufail Saputra. This institution aims to invite Muslims back to the Al-Qur'an with emphasis on understanding, appreciation and practice in daily life. Majlis Tafsir Al-Qur'an (MTA) has many contribution in the interpretation of the Al-Qur'an, assuredly has a view towards understanding the Hadith of the Prophet, especially about interpreting the Al-Qur'an with al-ra'y